PEMBENTUKAN KARAKTER BERBASIS KETELADANAN GURU DAN PEMBIASAAN MURID SIT AL BIRUNI JIPANG KOTA MAKASSAR - SUKMA, A.SUKMAWATI (Universitas Nahdatul Ulama Surabaya, 2020)
Character building has been widely proclaimed by educational institutions. The teacher has a special position in shaping character values ​​to create a generation of noble character. This study aims to determine the character formation based on teacher exemplary and student habituation. This research is a qualitative type of phenomenological research. Data collection techniques carried out by observation, in-depth interviews, and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. The results showed that the teacher's example was done through actions, such as discipline, maintaining success, being fair, wise, polite, polite in speaking, while students were accustomed to the school culture of greeting, salim, smile and greet, discipline, various religious activities, responsible, independent, honest and literacy activities. The impact caused after the teacher exemplary and habituation of students gives birth to characters such as creating creative humans, increasing faith, changing attitudes, and increasing reading fondness and environmental awareness